(untitled) (Journal of Hama University, 2022)
Objectives:The aim of this laboratory study was to evaluate the effect of different irrigation protocol using passive ultrasonic irrigation(PUI)and non-activated irrigation (NAI) and different root canal sealers using Bioceramic (MTA fillapex),and Resin-based sealers (ADSEAL) on the fracture resistance of endodontically treated teeth . Materials and Methods: Fortieth extracted mandibular premolars were selected with completed, straight and single canal roots and free of caries or resorption or any previous treatment. The tooth crowns were removed and root length was adjusted to 16mm,after preparation teeth were devided into four groups of 10 teeth each. Group I: irrigation with PUI and obturation with MTA fillapex . Group II: irrigation with NAI and obturation with MTA fillapex Group III : irrigation with PUI and obturation with ADSEAL . Group IV(control group): irrigation with NAI and obturation with ADSEAL. The root were vertically loaded with testing machine (Tinius Olesn H50KS) and the load when fracture was detected was recorded in newton. ANOVA test was used to show the nature of difference of the fracture load of studied groups.All statical analysis was performed at 95% level of confidence. The results showed group I higher resistance to fracture than other groups.and group V showed the least fracture resistance than other groups.Conclusion: Based on this in vitro study,PUI was more effective when compared with NAI ,and Bioceramic-based sealer was more effective when compared with Resin-based sealers .Clinical significance: The use of passive ultrasonic irrigation and bioceramic sealer enhanced the fracture resistance of endodontically treated teeth.